The relationship between motivation, perceived Motivational Climate, Task and Ego Orientation, and Perceived Coach Autonomy in young ice hockey players - ARNE MARTIN JAKOBSEN (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: This study is grounded in the theory of self-determination, the achievement goal theory, and the theory of perceived motivational climate. The goal of the study was to examine the relationships among perceived coach autonomy, motivation, task and ego orientation, and the perceived motivational climate in young ice hockey players. Material and methods: The participants included 401 ice hockey players aged 14-18 years old. To calculate the power of prediction between the independent variable "perceived autonomy from the coach", all 6 factors of motivation in the self-determination theory (SDT) and the goal orientation we conducted two path diagrams: one where task environment was the dependent variable and one with ego environment as the dependent variable. Between these factors and goal orientation among the players and the dependent variables, a hierarchical regression analysis was employed. Results: We found that high perceived autonomy support from the coach positively influences motivation in junior hockey players. Players who perceive autonomy support from their coach have a higher chance of scoring highly for autonomic regulation, according to self-determination theory. Conclusions: This probably leads to more task-oriented players who create a more task-oriented environment, hopefully resulting in fewer players dropping out of the sport.